ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF EXTRACTS OF SOURSOP (ANNONA MURICATA L.) LEAVES AND FRUIT PULPS - Pragati Balasaheb Khilari; Dr. Sadashiv Narayan Bolbhat (The Bioscan, 2024)
Annona muricata's role in healthcare has been better understood thanks to recent scientific and technological developments. Acetogenins, coumarins, phenolic acids, alkaloids, and flavonoids are among the phytochemical components. Antioxidants, antimicrobials, anti-diabetes, and a host of other health advantages are provided by the phytochemical composition. The purpose of this research was to detect phenolic and flavonoid phytochemicals in extracts from the leaves and pulp of the Annona muricata plant, as well as to compare and contrast the two components' antioxidant and antimicrobial capabilities. A Annona muricata tree was used to harvest the pulp and remove the leaves. The disc diffusion technique was used for antimicrobial testing against S. aureus, and antioxidant assays such as FRAP, DPPH, and TPC were performed. The investigation included samples with concentrations of 25, 50, 100, 200, and 400 μg/ml. The research found that different concentrations of 25μg, 50μ100μg, 200μ, and 400μg of extracts from the leaves and pulp of Annona muricata had a satisfactory level of antioxidants. The antibacterial activity of both extracts is effectiv e at such concentrations, however. When looking at the antioxidant content and sensitivity to microbes in the pulp and leaves extracts, the leaves extract comes out on top.